جودة الحياة الوظيفية وعلاقتها بالالتزام التنظيمي - جباريه شكيمه; سعاد جرمون (جامعة الوادي - University of Eloued, 2025)
"هدفت الدراسة الحالية للتعرف على العلاقة بين جودة الحياة الوظيفية والالتزام التنظيمي وكذا معرفة طبيعة العلاقة بين كل بعد من ابعاد جودة الحياة الوظيفية المتمثلة في الأجور المكافآت ،المشاركة في اتخاذ القرار، نمط الاشراف والالتزام التنظيمي لدى عينة من الموظفين الإداريين لمديرية الخدمات الجامعية بولاية الوادي، وقد تم استخدام المنهج الوصفي للدراسة، كما تم تصميم استبانة الدراسة كوسيلة لجمع البيانات اللازمة وتوزيعها على عينة الدراسة باستخدام طريقة العينة العشوائية حيث تم توزيع (110) استبانة على موظفين محل الدراسة وتم استرداد (100) استبانة، ولتحليل البيانات واختبار الفرضيات تم استخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية (SPSS25) . وقد أظهرت الدراسة النتائج التالية:  توجد علاقة ارتباطية ذات دلالة إحصائية بين جودة الحياة الوظيفية والالتزام التنظيمي داخل مديرية الخدمات الجامعية بالوادي.  توجد علاقة ارتباطية ذات دلالة إحصائية بين الاجر والمكافآت) والالتزام التنظيمي داخل مديرية الخدمات الجامعية بالوادي.  توجد علاقة ارتباطية ذات دلالة إحصائية بين المشاركة في اتخاذ القرارات والالتزام التنظيمي داخل مديرية الخدمات الجامعية بالوادي.  توجد علاقة ارتباطية ذات دلالة إحصائية بين نمط الاشراف والالتزام التنظيمي داخل مديرية الخدمات الجامعية بالوادي. "The current study aimed to identify the relationship between quality of career and organizational commitment, as well as to know the nature of the relationship between each dimension of quality of career, represented by participation in decision-making, wages, rewards, pattern of supervision and organizational commitment among a sample of administrative employees of the Directorate of University Services in the state of El Oued .The descriptive approach was used for the study, and the study questionnaire was designed as a means of collecting the necessary data and distributing it to the study sample using the random sample method (110) questionnaires were distributed to the employees under study, and (100) questionnaires were retrieved .To analyze the data and test hypotheses, the Statistical Package for the Social Sciences (SPSS) program was used. The study showed the following results:  There is a statistically significant correlation between quality of career and organizational commitment within the University Services Directorate in Al Wadi.  There is a statistically significant correlation between wages and rewards and organizational commitment within the University Services Directorate in Al Wadi.  There is a statistically significant correlation between participation in decision-making and organizational commitment within the University Services Directorate in Al-Wadi.  There is a statistically significant correlation between the pattern of supervision and organizational commitment within the University Services Directorate in Al-Wadi.
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع تنظيم وعمل
Keywords: العلاقة; الالتزام التنظيمي; جودة الحياة الوظيفية; quality of career; organizational commitment; relationship